Friend or Enemy: A Dual Role of Autophagy in Plant Virus Infection - Huang, Xiuqin; Chen, Siping; Yang, Xiaorong; Yang, Xin; Zhang, Tong; Zhou, Guohui (Frontiers in Microbiology, 2020)
Autophagy is a primary protective process that involves removing damaged organelles or dysfunctional proteins in eukaryotes. The autophagy pathway not only maintains cellular homeostasis, but also modulates the host’s cellular response to pathogen infection. Several studies have proved that autophagy plays a dominant role in plant fitness and immunity. As intracellular parasites, virus replication and spread entirely rely on the molecular machinery of the host cell, including the autophagy process. Plant viruses severely affect crop yields and quality. During infection, complex interactions exist between viral proteins and host factors in relation to plant defense and virus counter-defense. An increasing number of studies have demonstrated that plants use autophagy to eliminate and inhibit viruses; meanwhile, some viruses have been shown to manipulate the process of autophagy to promote their own replication and survival in plant cells. In this review, we summarize recent advances in plant autophagy, with an emphasis on the role of autophagy in plant virus infection.